Politicizing Europe in times of crisis - Swen Hutter; Hanspeter Kriesi (Journal of European Public Policy, 2019)
This paper starts from the premise that the politicization of Europe is indicative of a new structuring conflict that involves a set of processes which put the national political community under strain. This structuring conflict has been emerging long before the Euro and refugee crises. However, these crises may have reinforced and potentially reshaped public conflicts within and across countries. Therefore, the paper traces the politicization of Europe during national election campaigns in fifteen countries from the early 2000s up to 2017. The analysis focuses on the way the multiple crises have affected the level of politicization, its driving forces, and the location of European issues in the political space. Overall, the results indicate a substantive increase in politicization, but they also point to strong region and crisis-specific varieties which should be considered in scholarly discussions on the relative impact of domestic conflicts on the future course of European integration.
Keywords: 330; politicization; Eurocrisis; refugee crisis; radical left; radical right